PENGARUH SIKAP KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL PEMODERATING (STUDI EMPIRIS DI UNIVERSITAS MUHAMMADIYAH MAKASSAR) - Wa Ode Rayyani (AkMen JURNAL ILMIAH, 2019)
This research departs from the large demands for performance, where universities are expected to be able to produce output from quality performance. Therefore, this study is intended to describe the influence of work attitudes and work culture on performance by being moderated by motivational variables. This research is an empirical study conducted at the Muhammadiyah University of Makassar. As for data collection using survey methods through questionnaires aimed at Muhammadiyah University Makassar lecturers / employees as many as 60 people were selected by purposive sampling. The analytical method used is Multiple MRA (Moderated Regression Analysis). The hypothesis proposed is based on the expectation of the influence of work attitudes and organizational culture on the performance of higher education by being moderated by motivational variables. The results of the study indicate that there is a significant influence between work attitudes and organizational culture on performance. The existence of the moderating variable namely the motivation variable further strengthens the interaction of the influence of work attitude variables on performance, as well as the interaction of the influence of organizational culture variables on performance.